Efektivitas Intervensi Applied Behavior Analysis terhadap Perilaku On-Task Siswa ADHD di Sekolah Inklusi - Tri Gunadi (Hayati : Jurnal Pendidikan, 2026)
This study aims to examine the effectiveness of Applied Behavior Analysis (ABA)-based behavioral intervention in improving on-task behavior and instruction compliance among students with Attention Deficit Hyperactivity Disorder (ADHD) in an inclusive Islamic elementary school. The study employed a Single Subject Research (SSR) A–B–A–B reversal design with one male student aged 8 years (Grade 2) who was identified with Combined-type ADHD based on formal psychological assessment. Data were collected through direct observations across 20 sessions distributed across four research phases. The observation instrument was validated through expert judgment (Aiken’s V = 0.88) and demonstrated adequate interobserver reliability (mean IOA = 87.5%). Results indicate that on-task behavior improved from a mean of 36% during the first baseline phase (A1) to 70% during the second intervention phase (B2), while instruction compliance increased from 40% (A1) to 72.6% (B2). Visual analysis of the SSD graph yielded a Percentage of Non-overlapping Data (PND) of 100% for both intervention phases, indicating a highly effective intervention effect. These findings suggest that ABA is an effective strategy for improving academic engagement among students with ADHD in inclusive educational settings, with practical implications for classroom behavioral management.